PENGARUH FINANCIAL DISTRESS (ALTMAN Z-SCORE) DAN DEBT EQUITY TO RATIO TERHADAP RETURN SAHAM SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2018 - Caparino, Olivia; Simamora, Saur C (JURNAL ILMIAH M-PROGRESS, 2020)
This study aims to determine The Effect of Financial Distress and Debt Equity to Ratio on Stock Returns of Banking Sub Sector Listed in Indonesia Stock Exchange in 2018. Samples were taken using purposive sampling technique. Numbers of sample are 39 companies from 45 banking sub-sector companies in Indonesia Stock Exchange in 2018. The methods used for collecting data were documentation or secondary data. And for analysis technique used is multiple linear regression analysis and classic assumption test.Based on the results of the T test, it was concluded that Financial Distress had a positive and significant effect on Stock Return and Debt Equity to Ratio had a positive and significant effect on Stock Return. Based on the F test it was concluded that Financial Distress and Debt Equity to Ratio had a positive significant effect.Keywords: Investment, Financial Distress, Debt Equity to Ratio, Stock Return.